2006
DOI: 10.2337/dc06-0938
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Concentration of Remnant Lipoprotein Cholesterol in Obese Children and Adolescents

Abstract: OBJECTIVE -Remnant lipoproteins (RLPs) are the products of the lipolytic degradation of triglyceride-rich lipoproteins produced by the liver and intestine. Recent studies have demonstrated that RLPs are correlated with cardiovascular risk. We assessed the relationship between obesity and RLP and evaluated the factors related to RLP in children and adolescents.RESEARCH DESIGN AND METHODS -We measured BMI, waist circumference, blood pressure, body fat mass, total abdominal fat, visceral and subcutaneous fat area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Choi et al [59] have suggested that low density lipoprotein particle size negatively correlates with BMI. Remnant lipoprotein cholesterol, which is the product of the lipolytic degradation of triglyceride-rich lipoproteins produced by the liver and intestine, was previously shown to be higher in obese children and adolescents [6061]. In addition, obese children and adolescents had higher blood pressure readings than their peers of a normal weight [62].…”
Section: Physical and Psychological Comorbiditiesmentioning
confidence: 99%
“…Choi et al [59] have suggested that low density lipoprotein particle size negatively correlates with BMI. Remnant lipoprotein cholesterol, which is the product of the lipolytic degradation of triglyceride-rich lipoproteins produced by the liver and intestine, was previously shown to be higher in obese children and adolescents [6061]. In addition, obese children and adolescents had higher blood pressure readings than their peers of a normal weight [62].…”
Section: Physical and Psychological Comorbiditiesmentioning
confidence: 99%
“…A detailed description of the study design and methods is provided in a previous report [23]. Briefly, 135 children and adolescents (67 boys, 68 girls) were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies performed were focused on children and adolescents with obesity, diabetes mellitus or chronic inflammatory bowel diseases (Levy et al, 2000;Glowinska et al, 2003;Bueno et al, 2006;Choi et al, 2006;Pinhas-Hamiel et al, 2007;Guven and Sanisoglu, 2008). Only the Spanish (Food and Assessment of the Nutritional Status of Adolescents AVENA) cross-sectional study assessed age-and sex-specific serum lipid profiles in 581 healthy adolescents (Ruiz et al, 2006a, b), but its study population was limited to Spain.…”
Section: Introductionmentioning
confidence: 99%